Harnessing the power of failure : using storytelling and systems engineering to enhance organizational learning - Newman, John Steven; Wander, Stephen M. (Emerald Publishing Limited, 2018)
Failure informs more generously and reliably than success. Failure is the best indicator of whats working and whats not in any complex system or enterprise. All failures will inevitably reveal latent defects and/or failure modes that are invariably buried within the people, processes, materials, design, manufacturing, and management that comprise the complex system. In this new framework from former NASA aerospace professionals, Newman and Wander employ a unique system failure case study (SFCS) paradigm, originally developed to stimulate systems thinking and lessons learning at NASA, that combines storytelling and systems engineering designed to enhance organizational learning.The authors employ the SFCS approach to explore a vast array of failure events in multiple sectors of transportation, industry, aerospace, construction, and critical infrastructure. They provide an Integrated Analysis seeking trends, patterns, and universally applicable insights that readers can use to recognize areas of potential vulnerability within their own activities. The authors then identify specific actions within the span of control of enterprise leaders, project managers, process owners and operators which can be implemented to manage risk in high consequence, high risk activities.
Includes index.
Includes bibliographical references.
Print version record
Keywords: Success in business; Organizational learning; Business & Economics -- Strategic Planning; Business strategy